P–574 Examination of inter centre variation in PGT-A "no result rate" and efficacy of rebiopsy - Analysis of 22, 833 samples 2015–2019. (6th August 2021) - Lynch, C; Sanders, K; Gordon, T; Griffin, D
Abstract: Study question: Are there significant differences in PGT-A "no result" rates and clinical outcomes following rebiopsy between ART clinics, and do rebiopsied embryos perform better than transferring with no result? Summary answer: There is significant differences between clinics in terms of "no result rate" in PGT-A and utilisation of rebiopsy. What is known already: With any testing platform used in PGT-A, there is always a chance that a sample will not yield a result and rebiopsy may be considered to ascertain an embryos cytogenetic status. Studies have demonstrated rebiopsy yields results and adds to embryos genetically suitable for transfer. Clinical outcome data, however, remains scarce, leading to difficulty for clinics in benchmarking their performance when rebiopsied embryos are transferred. Study design, size, duration: A retrospective analysis was performed of trophectoderm samples submitted for PGT-A via NGS over a 5yr period, 2015–2019. The no result (NR) rate was calculated per year and per clinic. Clinics were contacted for follow up data on NR embryos in terms of usage and clinical outcomes. Clinical outcomes from rebiopsied embryos were compared with those transferred as NR without rebiopsy. Participants/materials, setting, methods: Data was collected on 22833 trophectoderm samples, submitted by 30 IVF laboratories. NR rate was analysed by year and by clinic. Clinics were asked if NR embryos had undergone rebiopsy, and if so if they had survived warming and rebiopsy. Clinics were asked if embryos selected for transfer had survived (re)warming, and to provide clinical follow-up including hCG test, clinical pregnancies, miscarriage and livebirth. The two tailed Fishers exact test was used for statistical analysis. Main results and the role of chance: There was a wide range in sample numbers submitted by clinics over the time period, ranging from 9 samples through to 2633. In tclinics submitting over 500 samples the NR rate ranged from 0.6% to 7.4%, and in the those submitting 100–499 samples it ranged from 1.1% to 5.8%. Both these differences proved to be statistically significant (p < 0.05) between the best and worst performing clinics, and shows that a gap in performance exists between clinics. Less than 50% of NR embryos underwent rebiopsy. While the majority of embryos undergoing rebiopsy yielded a result (92.3%) and 31.4% of these were euploid or mosaic, almost half still remain in storage. The rate of livebirth/ongoing implantation in the rebiopsy group is 35.5% and 17.1% in the non rebiopsy group, illustrating a non significant trend towards a higher chance of implantation and livebirth in the rebiopsy group. Of 58 patients undergoing rebiopsy without any euploids in their initial cycle, 18 had a euploid embryo identified for future use. The additional manipulations involved in rebiopsy do not impact on survival at warming for transfer, but clinical outcomes in rebiopsied embryos appear poorer than those where a result was generated at first biopsy. Limitations, reasons for caution: Despite starting with 22833 samples, 1115 of which were classified as NR, there were only 31 rebiopsied and 42 NR embryos transferred. It was therefore not possible to analyse transfer data by clinic or by embryo quality. Wider implications of the findings: Rebiopsy yields genetic results and embryos suitable for patient use, including for patients who produced no other euploid/mosaic embryos in their cycle. However, it is not offered/performed in many cases. Clinical outcome data must continue to be compiled and analysed to confirm performance exceeds transfer of NR embryos. Trial registration number: Not applicable